Undeserving heirs: how the origins of wealth shape attitudes towards redistribution - Becker, Bastian; Waitkus, Nora (European societies, 2025)
Inherited wealth has often been accumulated under circumstances seen as undeserving by present-day standards. However, there is surprisingly little knowledge about the political consequences of wealth's history. We argue that illegitimate accumulation nurtures opposition and calls for redistribution, even after multiple generations. To test our theory, we conduct a survey in Germany, where many wealthy business owners inherited companies that made large fortunes during one of the darkest episodes of human history, the Nazi regime of 1933-1945. We demonstrate with a vignette experiment that individuals perceive heirs of businesses that cooperated with the Nazi regime to be less deserving than other similar heirs, and that they are more likely to support the targeted redistribution of such inherited business wealth. Therefore, undeservingness can be inherited and passed on from one generation to another. These results align with general views and attitudes about the German economy. Our findings add to studies on the historical origins of public opinion as well as deservingness by showing how illegitimate wealth accumulation affects political attitudes across generations.
Gesehen am 20.02.2026